IMPLEMENTASI APLIKASI PERHITUNGAN GAJI PEGAWAI PADA PERUSAHAAN AIR MINUM (PDAM) KABUPATEN PONOROGO - Lutfiyah Dwi Setia (Department of Science and Technology Ibrahimy University, 2017)
In the process of salary accounting at the PDAM Kab Ponorogo, has been computerized so far but, not effective yet. Because the institution is still using manually program the antire data must be input one by one. Such system is less helpful in the process of the salary payment accounting. Because, when inputing the data one the mistakes occure very often. To overcome such problem the writer has arranged a system of the salary accounting application. The methode of developing system applied by the writer concists of several stages. They are data accumulating, designing and testing. On the stage of designing system includes files planning, design input and design output. After implementing all application planning into the term of program java netbeans version 8.0, it would be obtained the salary accounting system. By using this system, it is expected to be helpful to the Department of financial. Especially in the process of salary accounting application at the PDAM Kab. Ponorogo.